Phenological Study of Flowering and Fruiting in Banana “Rejang” (Musa acuminata Colla) - Asmah, Nur; Widodo, Winarso Drajad; Suketi, Ketty (Journal of Tropical Crop Science, 2025)
Banana “Rejang” originates from Rejang Lebong Regency in Bengkulu Province, Sumatra, at elevations ranging from 600 to 700 meters above sea level. Banana “Rejang” is known for its sweet taste, high fibre in the pseudo stems, resistance to Fusarium spp., with slender and long fruits, and tapering fruit tips. This study aims to examine the phenological patterns of Rejang bananas and establish appropriate harvest criteria using the heat unit method. A descriptive research design was employed to illustrate the phenological development during the generative phase without external treatments. A total of 25 Rejang banana plants were observed and measured, spanning the developmental stages from flag leaf emergence to flowering and fruiting. Data were collected daily at 7:00 a.m., 10:00 a.m., 1:00 p.m., and 4:00 p.m. The average daily temperature was recorded to calculate heat units in degrees Celsius (°C). Phenological development begins with the emergence of the flag leaf at 102 days after planting, corresponding to an accumulated heat unit of 1,800-degree days. Flower initiation occurs at 134 days after planting, with 2,330-degree days accumulated as heat units. The period from flower initiation to anthesis lasts approximately 4 days, followed by a period of 4 days after anthesis (DAA). Bract opening occurs 3 DAA, followed by bract rolling at 7 DAA and banana heart emergence at 10 DAA. The bunch stalk forms 7 days after anthesis, after the banana heart emerges. Fertilization occurs 165 days after planting (DAP), with a total heat unit accumulation of 2,833 degree-days. This stage involves the formation of the bunch stalk and the emergence of the fruit cluster, which occurs 5 DAA. The rachis appears at 5 days after anthesis, and fruit development is reached at 12 DAA after rachis emergence. The optimal harvest.